When hospitality brands go green: the role of authenticity and stereotypes in building customer-green brand relationships - Chua, Bee-Lia; Kim, Seongseop (Sam); Baah, Nancy Grace; Moon, Hyoungeun; Yu, Jongsik; Han, Heesup (Routledge, 2024)
Drawing on the logic behind customer-brand relationships, this study presents a model outlining the role of brand authenticity in the context of green hospitality brands. A cross-sectional survey was administered to 352 Korean consumers who visited green hospitality premises. The results indicated that functional qualities and stakeholder involvement are essential to building perceived green brand authenticity. The study supported that an authentic green brand is instrumental in increasing customer beliefs about its warmth and competence. Surprisingly, the results showed that evaluating a green brand as warm is the key to building green brand trust, while found a non-significant influence of green brand competence on green brand trust. This study also provided evidence that when green brand trust is formed, its effect on both green brand love and green brand identification is noticeable, which then translates into green brand choice. Overall, this study enriches the significance of the perception of green brand authenticity in fostering a favorable relationship between customers and green brands. In green brand management, brand stereotypes play a dual role in the brand choice formation. Furthermore, contextually induced green stimuli, which include operations, employee behavior, and customer engagement, are required to influence customer perception of green brand authenticity. © 2023 Informa UK Limited, trading as Taylor & Francis Group.